2014
DOI: 10.3109/07420528.2013.864301
|View full text |Cite
|
Sign up to set email alerts
|

Thoracic surface temperature rhythms as circadian biomarkers for cancer chronotherapy

Abstract: The disruption of the temperature circadian rhythm has been associated with cancer progression, while its amplification resulted in cancer inhibition in experimental tumor models. The current study investigated the relevance of skin surface temperature rhythms as biomarkers of the Circadian Timing System (CTS) in order to optimize chronotherapy timing in individual cancer patients. Baseline skin surface temperature at four sites and wrist accelerations were measured every minute for 4 days in 16 patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 50 publications
2
32
0
2
Order By: Relevance
“…Analysis of wrist temperature has been used in the circadian assessment of human subjects in studies measuring sleep quality, blood pressure, aging, cancer therapeutics, and weight loss (Bandin et al, 2014; Blazquez et al, 2012; Corbalán-Tutau et al, 2011; Gompper et al, 2010; Roche et al, 2014; Romeijn & Van Someren, 2011; Sarabia et al, 2008; Yoon et al, 2003). These temperature rhythms have been shown to correlate with changes in dim light melatonin onset, a standard for determining circadian phase in people (Nováková et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Analysis of wrist temperature has been used in the circadian assessment of human subjects in studies measuring sleep quality, blood pressure, aging, cancer therapeutics, and weight loss (Bandin et al, 2014; Blazquez et al, 2012; Corbalán-Tutau et al, 2011; Gompper et al, 2010; Roche et al, 2014; Romeijn & Van Someren, 2011; Sarabia et al, 2008; Yoon et al, 2003). These temperature rhythms have been shown to correlate with changes in dim light melatonin onset, a standard for determining circadian phase in people (Nováková et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, night time inactivity and removal of the device can be difficult to distinguish. Some recent studies suggested that core temperature is more robust biomarker for circadian rhythms than rest-activity spans, and hence (wireless) skin temperature measurement may provide a more precise measurement of circadian rhythms (Scully et al 2011;Roche et al 2014). However this method is still challenged by signal dropouts, ambient temperature interferences, and high costs.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, the administration of anticancer agents at the circadian time when they were the safest also achieved best efficacy both in rodents (4) and in cancer patients (5)(6)(7)(8). Large intersubject differences in CTS further need to be taken into account for the personalization of circadian delivery of cancer treatments (9,10). Thus, a systematic mapping of the critical pathways of anticancer drug chronopharmacology and their molecular clock control is required for optimizing treatment effects through tailoring circadian drug delivery to individual CTS.…”
Section: Introductionmentioning
confidence: 99%